2023
DOI: 10.1088/1361-648x/acc70f
|View full text |Cite
|
Sign up to set email alerts
|

Insights into selected 2D piezo Rashba semiconductors for self-powered flexible piezo spintronics: material to contact properties

Abstract: The new paradigm in electronics consists in realizing the seamless integration of many properties latent in nanomaterials, such as mechanical flexibility, strong spin-orbit coupling (Rashba spin splitting - RSS), and piezoelectricity. Taking cues from the pointers given on 1D ZnO nanowires [ACS Nano 2018, 12, 1811−1820], the concept can be extended to multifunctional 2D materials, which can serve as an ideal platform in next-generation electronics such as self-powered flexible piezo-spintronic device. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 104 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…flexibility, piezoelectricity, and Rashba spin splitting. 12 Katan and coworkers have investigated theoretically metal substitution based on available crystallographic data of tri-chloride CH 3 NH 3 MCL 3 (M = Pb, Sn, Ge) crystal structures, having a 3D inorganic network of corner-shared octahedra. 13 Furthermore, an investigation of bromide and iodide revealed that spin–orbit interaction stemming from halogens might also be significant, especially for iodide.…”
Section: Introductionmentioning
confidence: 99%
“…flexibility, piezoelectricity, and Rashba spin splitting. 12 Katan and coworkers have investigated theoretically metal substitution based on available crystallographic data of tri-chloride CH 3 NH 3 MCL 3 (M = Pb, Sn, Ge) crystal structures, having a 3D inorganic network of corner-shared octahedra. 13 Furthermore, an investigation of bromide and iodide revealed that spin–orbit interaction stemming from halogens might also be significant, especially for iodide.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric effect reflects the change of electric polarization with an external strain. Materials with piezoelectric effect have useful application prospects, such as sensors, transistors, energy harvesting systems, medical imagining, photocatalysts, , optoelectronics, , valleytronics, and self-powered piezo spintronics. , Since graphene, a single atomic layer of carbon, was successfully prepared in 2004, two-dimensional (2D) materials have attracted great interest due to their unique properties . The experimental detection of the piezoelectric effect of MoS 2 monolayer semiconductor material makes the 2D material with piezoelectric effect move from theory to reality. ,, Subsequently, the entrance of 2D piezotronics was opened.…”
mentioning
confidence: 99%
“…21 Fifth, it can be combined with the Rashba effect. 11,22,23 For example, CrSSe and CrSeTe monolayer are materials with both Rashba spin splitting and piezoelectricity, which may become efficient micronano spintronics. 22 Graphene and many other 2D materials (such as silicene and germanene, 24,25 graphynes, 26 borophene, 27,28 FeB 2 monolayer, 29 t-BN, 30 and M 3 X 2 31 ) constitute a special class of 2D materials called Dirac materials due to their characteristic cone-like band structure near the Fermi level, and the resulting low-energy excitations behave as massless Dirac fermions, 14,32,33 which further leads to various novel phenomena and properties such as fractional quantum Hall effect 34,35 and ultrahigh carrier mobility.…”
mentioning
confidence: 99%
See 2 more Smart Citations